Hierarchical Deep Learning for Malaria Diagnosis: Integrating YOLO-Based Detection and Uncertainty-Aware Cell Classification - Farias, Luciano Luz Beylouni; Mota, Mateus Balda; Becker, Karin; Recamonde-Mendoza, Mariana (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21624, 2026)
Malaria diagnosis through optical microscopy of blood smears remains the gold standard but is labor-intensive and subject to inter-observer variability. This study proposes a hierarchical deep learning pipeline that integrates cell detection in microscope field of view (FoV) images with classification of individual red blood cells. YOLOv8 is used to detect candidate cells and the extracted regions are classified by convolutional neural networks with uncertainty quantification and Grad-CAM explainability. MobileNetV2 achieved 95.17% accuracy in the classification of isolated cells with efficient prediction sets. However, under domain shift conditions, conformal prediction revealed a drop in reliability (coverage from 95% to approximately 86%), indicating reduced generalization. Grad-CAM analysis also revealed the Clever Hans effect, where models relied on image artifacts rather than biological features. These results highlight the importance of integrating reliability and explainability mechanisms for computer-aided malaria diagnosis.